Analisis Risiko Keselamatan dan Kesehatan Kerja Menggunakan Metode Hirarc pada Proses Perbaikan Kapal Tugboat (Studi Kasus PT Marga Surya Shipindo, Samarinda) - Willy Tambunan (Universitas Medan Area, 2019)
Health and safety has been known as one of the requirements in carrying out tasks and a form of human rights factor for workers in carrying out work activities. Lack of awareness and concern for K3 resulted in the existence of work risks, namely the presence of accidents that occur in welding activities carried out on the maintenance of tugboats carried by PT. Margasurya Shipindo like being hit by welding sparks, slipping, touched by hot iron which causes injury to workers. Therefore the purpose of this study is to identify and classify potential hazards, and control risks in work activities at PT. Marga Suryashipindo. Hazard analysis of risk in this study used the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. Based on the results of observations and interviews with 3 maitenance workers and 1 maintenance coordinator, there were 22 potential hazards. Based on the risk assessment, the risk level values were not with the HIGH category, 10 risks were MEDIUM category and 12 risk were LOW category. Control of the above risks is to use APD with the standards of welding workers, carry out administrative controls in the form of the application of SOP welding and K3 supervision to evaluate work activities. In addition, Engineering control is also carried out in the form of holding lift aids and doing maintenance on a regular basis, procuring toolsbox, and arranging tools and materials in the welding location.